2006
DOI: 10.1111/j.1834-7819.2006.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention procedures for stabilizing tooth position after treatment with orthodontic braces

Abstract: Background:Retention is the phase of orthodontic treatment that attempts to keep teeth in the corrected positions after treatment with orthodontic (dental) braces. Without a phase of retention there is a tendency for the teeth to return to their initial position (relapse). To prevent relapse almost every patient who has orthodontic treatment will require some type of retention. Objectives: To evaluate the effectiveness of different retention strategies used to stabilize tooth position after orthodontic braces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
1
22
0
3
Order By: Relevance
“…Littlewood et al 3,4 provide some of the best contemporary evidence available on retention, having conducted a systematic review of the literature.…”
Section: Commentary and Analysismentioning
confidence: 99%
“…Littlewood et al 3,4 provide some of the best contemporary evidence available on retention, having conducted a systematic review of the literature.…”
Section: Commentary and Analysismentioning
confidence: 99%
“…7,8 Although these retainers are widely used, only a limited number of studies can be found concerning their long-term effectiveness. In a Cochrane review, 9 there was only one randomized clinical trial 10 that assessed the mandibular incisor alignment after 3 years of retention.…”
Section: Introductionmentioning
confidence: 99%
“…It's purely a waste of time if a perfectly done fixed orthodontic treatment is not stable after debonding. In orthodontics, retention can be defined as the phase of orthodontic treatment that attempts to keep teeth in their corrected position following orthodontic therapy, and is thus a very integral part of the treatment [1]. In cases, where proper retention was not gained during post treatment phase, relapse occurs.…”
Section: Introductionmentioning
confidence: 99%
“…It takes a minimum of 232 days for fibers around the teeth to remodel to the new position [3]. To minimize the incidence of relapse it is vital for the all patients who have orthodontic treatment to use some type of retainer [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation